2009
DOI: 10.1038/emboj.2009.241
|View full text |Cite
|
Sign up to set email alerts
|

NEMO specifically recognizes K63-linked poly-ubiquitin chains through a new bipartite ubiquitin-binding domain

Abstract: An important property of NEMO, the core element of the IKK complex involved in NF-jB activation, resides in its ability to specifically recognize poly-ubiquitin chains. A small domain called NOA/UBAN has been suggested to be responsible for this property. We recently demonstrated that the Cterminal Zinc Finger (ZF) of NEMO is also able to bind ubiquitin. We show here by ZF swapping and mutagenesis that this represents its only function. While neither NOA nor ZF shows any preference for K63-linked chains, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 53 publications
(99 reference statements)
5
143
0
Order By: Relevance
“…Cordier et al [96] demonstrated that the NEMO ZF is a ubiquitin-binding module. Moreover, the ZF helps to establish the specificity of the NOA/NUB/ UBAN domain toward K63-linked polyubiquitin chains [97]. Whether the role of the ZF in promoting NEMO SUMOylation is mechanistically related to the regulation of monomer-dimer states of free NEMO and/or its ubiquitin-binding activity needs to be investigated.…”
Section: Roles Of Nemo Zf Domain and Sumo1mentioning
confidence: 99%
“…Cordier et al [96] demonstrated that the NEMO ZF is a ubiquitin-binding module. Moreover, the ZF helps to establish the specificity of the NOA/NUB/ UBAN domain toward K63-linked polyubiquitin chains [97]. Whether the role of the ZF in promoting NEMO SUMOylation is mechanistically related to the regulation of monomer-dimer states of free NEMO and/or its ubiquitin-binding activity needs to be investigated.…”
Section: Roles Of Nemo Zf Domain and Sumo1mentioning
confidence: 99%
“…However, it was proposed that the C terminus of NEMO, comprising the UBAN and the ZnF, has a higher affinity toward Lys-63-and Lys-48-linked ubiquitin chains consisting of three or more ubiquitin moieties (25). To elucidate the ubiquitin binding preferences of full-length NEMO we performed in vitro binding studies with bacterially purified recombinant fulllength NEMO and ubiquitin chains of different linkage types and lengths.…”
Section: Full-length Nemo Preferentially Binds To Linear Ubiquitinmentioning
confidence: 99%
“…18 Interestingly, a constitutively active GTP-bound mutant of Rab8 (Q67L) but not a with its activity. 5,8 Zhu and colleagues have proposed that, following TNFα stimulation, Optn would compete with NEMO for binding to polyubiquitinated substrates (such as RIP1, Table 1), therefore downregulating NFκB activation. 9 Accordingly, a point mutation Asp 474 →Asn (D474N) in the UBD of Optn abolished its binding activity to Lys63-linked polyUb and prevents its interaction with RIP1.…”
Section: Biological Processes Involving Optineurinmentioning
confidence: 99%